2014
DOI: 10.3390/pr2020466
|View full text |Cite
|
Sign up to set email alerts
|

Microreactors for Gold Nanoparticles Synthesis: From Faraday to Flow

Abstract: Abstract:The seminal work of Michael Faraday in 1850s transmuted the "Alchemy of gold" into a fascinating scientific endeavor over the millennia, particularly in the past half century. Gold nanoparticles (GNPs) arguably hold the central position of nanosciences due to their intriguing size-and-shape dependent physicochemical properties, non-toxicity, and ease of functionalization and potential for wide range of applications. The core chemistry involved in the syntheses is essentially not very different from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 83 publications
(88 reference statements)
0
36
0
Order By: Relevance
“…These have all been found to influence the products. An extensive review on the subject is covered elsewhere 37 and have been extensively applied to the production of AuNPs 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have all been found to influence the products. An extensive review on the subject is covered elsewhere 37 and have been extensively applied to the production of AuNPs 38 .…”
Section: Introductionmentioning
confidence: 99%
“…organic) and a metal precursor in the second phase (e.g. aqueous) as shown in (Figure 1Di) and a wide range of synthetic strategies at these interfaces have been reported 37,38,59,60 .…”
Section: Introductionmentioning
confidence: 99%
“…Microreactors offer a small volume for the reaction, which allows precise control over the synthesis of nanoparticles such as palladium (Pd), platinum (Pt) and gold (Au) etc. [16][17][18]. Rebrove et al [19] have shown that a microreactor system increases the heat transfer within the reaction mixture and hence improves the reaction kinetics.…”
Section: Introductionmentioning
confidence: 97%
“…Exactly this is the focus of the current special issue "Design and Engineering of Microreactor and Smart-Scaled Flow Processes" of the journal "Processes". This special issue comprises three review papers, five research articles and two communications.Rahman and Rebrov have presented an overview of the application of microreactors in the synthesis of gold nanoparticles (GNP) [1]. Considering that reactant mixing is one of the most critical factors influencing the GNP synthesis, batch operating conditions commonly pose great limitations to both quality and scalability of the process.…”
mentioning
confidence: 99%
“…Rahman and Rebrov have presented an overview of the application of microreactors in the synthesis of gold nanoparticles (GNP) [1]. Considering that reactant mixing is one of the most critical factors influencing the GNP synthesis, batch operating conditions commonly pose great limitations to both quality and scalability of the process.…”
mentioning
confidence: 99%